(untitled) (Czech Journal of International Relations, 2016)
In 2012, Islamist violent non-state actors in northern Mali succeeded in fighting against the Malian army, and they got the entire north Malian territory under their control. This paper seeks to answer the question of why the Islamists were dislodged and the territory was brought back under the control of the Malian state only after a time gap of one year. Using the theoretical conception of an enemy centric approach, the criteria of competence, willingness, empowerment, and the successful execution of the counterinsurgency military operation are conceptualized. The paper uses this research framework to analyze the actions of the three counterinsurgency actors – Mali, ECOWAS/CÉDÉAO, and France – and explains the above-mentioned gap. The research shows that IVNSAs were eliminated and the ability of the (Malian) state to control the territory was restored only when the counterinsurgency actor (France) was able to accomplish the given criteria of competence, willingness, and empowerment simultaneously.